COGNITIVE IMPAIRMENT AND DEPRESSION ARE THE MOST IMPORTANT RISK FACTORS FOR FRAILTY - Hariyanti, Tita; Sunarti, Sri; Vistiandini, Seravina Ayu (Malang Neurology Journal, 2020)
Background: Frailty is a condition that causes a decline or failure in homeostasis mechanism on older people resulting in increased susceptibility to stressor. The risk factors of frailty include: cognitive impairment and depression.Objective: To prove the relation between cognitive impairment and depression with frailty.Methods: This study is using cross-sectional approach. Samples are collected from 222 citizens from the elderly population of Malang using accidental sampling method. Variables measured in this study are frailty that is determined by Fried Criteria, cognitive impairment that is determined by MMSE score and depression status that is determined by GDS score.Results: The analysis result of relation between cognitive impairment and depression and frailty using the Spearman correlation test produces the value of p = 0,000 and the correlation coefficients for rare 0,500 and 0,508 respectively. Different levels of cognitive impairment and depression in the frail group compared to pre-frail and robust groups resulted in p = 0,000, whereas the level of cognitive impairment and depression in the pre-frail group compared to robust group yielding p values of 0.735 and 0.944 respectively.Conclusion: There is a relation between cognitive impairment and depression on frailty. There was a significant difference in the levels of cognitive impairment and depression in the frail group compared to the pre-frail and robust groups, whereas in the pre-frail group compared to robust group the levels of cognitive impairment and depression did not have a significant difference.